If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15(-2x + -1y) = -15(-6) (-2x * -15 + -1y * -15) = -15(-6) (30x + 15y) = -15(-6) Multiply -15 * -6 30x + 15y = 90 Solving 30x + 15y = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15y' to each side of the equation. 30x + 15y + -15y = 90 + -15y Combine like terms: 15y + -15y = 0 30x + 0 = 90 + -15y 30x = 90 + -15y Divide each side by '30'. x = 3 + -0.5y Simplifying x = 3 + -0.5y
| 6y+10=y+3 | | 8-9y=89 | | 5(-4-4p)=18-p | | 9(2b+1)2b=29 | | 18=-9(v+5) | | y=-6x+14 | | 0=-4.9t^2+70 | | -9(v+5)=18 | | 1-x=3x-9 | | 3(4a+6)=2+28 | | sinx=90 | | X=4(70-X) | | -243=11x-100 | | -16v-72=15v+21 | | 0.875x=0.83333 | | 4x^2=1600 | | 2.3x+1.2+2.5x=9.2-3.2x | | 9-5[4-(9y-7)]= | | 5,300-500f=f | | 5,300-200f=f | | -15=m-3+2m | | 2(5y-6)=4[x-3(x-10)] | | 24=7m-6+8m | | 2n-3-3n=-5 | | B+3=b+2 | | -6b-6b=-24 | | 1x+5y=20 | | 2b+10=b+2 | | 2b+10=b+3 | | C-5d=2 | | 4b-2=18 | | 5,300f-3,200=f |